1989
DOI: 10.1111/j.1365-2826.1989.tb00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Arcuate Nucleus and Preoptic Area Involvement in Beta‐Endorphin‐lnduced Release of Prolactin in Conscious Ovariectomized Rats†

Abstract: The ability of 8-endorphin (/?-END) to release prolactin and t h e ability of naloxone to block prolactin's release when delivered to specific hypothalamic areas via push-pull perfusion was studied in unrestrained, conscious, ovariectomized rats. Perfusion of either the arcuate nucleus or the preoptic area with 8-END for 15 to 30 min caused a large, brief increase in plasma prolactin levels. Perfusion for a longer time period (120 min) resulted in peak prolactin levels at 60 min, with a return to baseline by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Although extrahypothalamic site(s) whereby endogenous opioids alter prolactin secretion cannot be excluded, the prevailing view of the locus of endogenous opioids' action asserts that it takes place at the hypothalamic level (1485,1836,1880). Indeed, chemical lesions within the arcuate nucleus by neonatal administration of monosodium glutamate impairs the ability of morphine to induce prolactin secretion (49) while the opiate antagonist naloxone diminishes the release of prolactin evoked by electrical stimulation of the medial basal hypothalamus (48).…”
Section: Neuropeptidesmentioning
confidence: 99%
“…Although extrahypothalamic site(s) whereby endogenous opioids alter prolactin secretion cannot be excluded, the prevailing view of the locus of endogenous opioids' action asserts that it takes place at the hypothalamic level (1485,1836,1880). Indeed, chemical lesions within the arcuate nucleus by neonatal administration of monosodium glutamate impairs the ability of morphine to induce prolactin secretion (49) while the opiate antagonist naloxone diminishes the release of prolactin evoked by electrical stimulation of the medial basal hypothalamus (48).…”
Section: Neuropeptidesmentioning
confidence: 99%
“…It seems that the endogenous opioid peptides exert their action at the hypothalamic level to alter PRL secretion (23)(24)(25). Although a nondopaminergic mechanism(s) may also be involved in the opiate stimulation of PRL release (26,27), a number of studies indicate that the endogenous opioid peptides interact with the TIDA neurons.…”
mentioning
confidence: 99%
“…Decreased responsiveness to a second infusion of (3-End was first reported when ovariectomized rats were treated with two perfusions of [3-End, 90 min apart, into the arcuate nucleus. A separate experiment showed that elevated PRL levels, in response to a 120-min perfusion of P-End, decreased dramatically after only 60 min of treatment [46]. Reduced sensitivity to [3-End could have perhaps taken place at the receptor level.…”
Section: Discussionmentioning
confidence: 95%